Robust position anti-interference control for PMSM servo system with uncertain disturbance - Li, Longfei; Xiao, Jie; Zhao, Yun; Liu, Kan; Peng, Xiaoyan; Luan, Haozhe; Li, Kaiqing (CES Transactions on Electrical Machines and Systems, 2020)
Aiming to suppress the influence of uncertain disturbances in the drive control of permanent magnet synchronous machines (PMSM), such as the parameter uncertainties and load disturbance, a robust anti-interference control for the angular position tracking control of a PMSM servo system has been proposed in this paper. During the position tracking, uncertain system disturbances being regarded as a lumped unknown term will be online observed by a nonlinear disturbance observer (NDOB), of which the influence will consequently be counteracted by a robust backstepping compensator (RBC). The asymptotical stability of proposed control scheme is analyzed and designed according to the Lyapunov stability criterion, and its convergence against the system uncertain disturbance is verified on a prototype PMSM servo platform and shows good performance in rotor angular position tracking and anti-interference.